(untitled) (Patan Prospective Journal, 2023)
This study looks at the changing trends and patterns of violence against women in Nepal from 1997 to 2020. The study examines particular types of violence, such as attempted rape, domestic violence, polygamy, trafficking, witchcraft, child marriage, and abortion. Data from the past two decades are analyzed using a quantitative research approach to look for any trends or patterns in the occurrence of various types of violence. The research’s overarching goal is to use statistical analysis to evaluate theories related to these trends in order to better understand the prevalence and fundamental characteristics of crimes against women in Nepal. To analyze the gathered data, the research approach uses descriptive statistics as well as hypothesis testing. The findings are interpreted in light of the existing body of knowledge and ongoing investigations into assaults against women. Different trajectories in the frequency of various forms of violence have been revealed by the data analysis. Over time, we’ve seen a decline in some forms of violence, like domestic violence. Others, such as attempted rape and human trafficking, have shown an upward trend. This study emphasizes how important it is to continue working to address the underlying issues that lead to violence against women. The importance of creating comprehensive programs that prioritize prevention, prompt intervention, and all-encompassing care for survivors is emphasized. The study ultimately serves as a call for continued commitment to the cause and comprehensive strategies for ending violence against women in Nepal. It adds to the ongoing conversation about the safety and wellbeing of women.